2018
DOI: 10.1140/epjc/s10052-018-6291-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-truncated strategy to exactly integrate the post-Newtonian Lagrangian circular restricted three-body problem

Abstract: In this study, we present a novel non-truncated strategy by accompanying the fixed-point iteration with traditional numerical integrators. The proposed non-truncated strategy aims to exactly integrate implicit motion equations that are directly derived from the Lagrangian of the post-Newtonian circular restricted three-body problem. In comparison with the commonly used truncated approach, which cannot exactly but approximately preserve the generalized Jacobian constant (or energy) of the original Lagrangian sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Here, the integrator, dynamical parameters and initial orbital elements in the above Kepler problem are still used. In the present case, the speed of light c = 10 4 just corresponds to the first order post-Newtonian effect, which is approximate to the magnitude of 10 −8 (compared to the main Kepler part) in the solar system (Dubeibe et al 2017;Huang et al 2018). 4 As shown in Figure 3, the new method M1 and the Fukushima's method M2 give the machine double precision ǫ = 10 −16 to the inclination I and the longitude of ascending node Ω.…”
Section: A Post-newtonian Two-body Problemmentioning
confidence: 52%
“…Here, the integrator, dynamical parameters and initial orbital elements in the above Kepler problem are still used. In the present case, the speed of light c = 10 4 just corresponds to the first order post-Newtonian effect, which is approximate to the magnitude of 10 −8 (compared to the main Kepler part) in the solar system (Dubeibe et al 2017;Huang et al 2018). 4 As shown in Figure 3, the new method M1 and the Fukushima's method M2 give the machine double precision ǫ = 10 −16 to the inclination I and the longitude of ascending node Ω.…”
Section: A Post-newtonian Two-body Problemmentioning
confidence: 52%
“…In fact, ẍ0 and ÿ0 should be ẍ and ÿ, respectively. In this way, there are implicit acceleration equations suggested in [12]. They are given coherently, and should be completely equivalent to Eqs.…”
Section: Pn Circular Restricted Three-body Problemsmentioning
confidence: 99%
“…There is a question of whether the coherent Lagrangian equations of motion can be written. Recently, the au-thors of [12] suggested that coherent implicit acceleration equations, derived from the Lagrangian of a PN circular restricted three-body problem [4,13], should be integrated by using implicit numerical integrators. Unlike them, we provide a simple method to construct the coherent Lagrangian equations of motion that strictly conserve the constants of motion.…”
Section: Introductionmentioning
confidence: 99%